The Vastgota laws
1 online resource
Keywords: The Vstgta Laws contains the translation of the oldest of the Swedish provincial law codes and other texts of great relevance to the legal history. The first version, the Older Vstgta Law, is from the first half of the thirteenth century and the earliest example of an indigenous vernacular literacy with the Latin script from Sweden. A second and highly revised version of the law is preserved in a manuscript from the middle of the fourteenth century. This volume also contains a translation of the annotations and proposals made during the complicated negotiations between representatives of the church, the kingdom, and the community of the province. Together, the two versions of the law and the annotations offer a unique possibility to understand the making and transformation of a medieval law. The importance of the regional leaders, the lawmen, is evident from the earliest example of history writing in Sweden, illustrating the legal and political history of Vstergtland. With an Introduction that places the province of Vstergtland and its law into its political setting, this translation is invaluable for all students and scholars of medieval Swedish legal and political history.